The Innovative and Budgetary Region Development based on the Public-private Partnership Mechanism - Matyushkina, Irina; Igolnikova, Inna; Pogonysheva, Dina; Mikhaleva, Olga; Fetshchenko, Valentina; Shchelikova, Natalia (International Journal of Economics and Financial Issues, 2016)
The paper has analyzed the consolidated budget dynamics of one of the Russian the regions during 2010-2014, studied the socio-economic development trend of the region, assessed the investment dynamics in fixed assets, and identified the changes in the number of the region organizations dealing with scientific researches. One of the analysis' directions is "organizational and economic regulation of the regions' development". The paper offers the certain recommendations how to optimize the investment and budgetary management of regional development based on the public-private partnership mechanism and gives reasons for the improving the organizational and economic measures dealing with the optimization of the budget management development in the region. Introducing the innovation development programs in the region, the financing of which requires the extensive financial resources, it is impossible to withdraw surplus funds from the local budgets of the region due to the following "slowdowning" of the innovation sector development in the region. Therefore, the vertical budget policy plays an important role in solving such issues. Keywords: innovative development, budgetary development, socio-economic development, regional development, public-private partnership JEL Classifications: F63, I25, R11